2012
DOI: 10.1007/s11053-012-9192-2
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Depletion of Oil and Gas Resources in Malaysia

Abstract: This paper provides an assessment of the changes in the availability of oil and gas resources in Malaysia. The physical and monetary balance sheets for crude oil and natural gas for the period 2000-2007 was constructed. The net present value of expected future incomes to reflect the value of resource change was calculated based on a physical extraction and a resource rent scenario. Resource rent is gross operating surplus less the estimated user cost of produced capital in the crude oil and natural gas extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Apart from that, Malaysia is also an active player in oil and natural gas industry, as well as other agricultural product such as natural rubber, palm oil, pepper, cocoa and marine fish (Vincent, 1997). Malaysia's source of income had depended largely on these resources especially the oil and natural gas (Othman & Jafari, 2012). However, the land-based mining industry had become stagnant as the tin market had crashed in 1980s and due to lack of exploration and development of the land-based minerals (Lee, 2013).…”
Section: Deep Seabed Minerals As the New Mineral Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from that, Malaysia is also an active player in oil and natural gas industry, as well as other agricultural product such as natural rubber, palm oil, pepper, cocoa and marine fish (Vincent, 1997). Malaysia's source of income had depended largely on these resources especially the oil and natural gas (Othman & Jafari, 2012). However, the land-based mining industry had become stagnant as the tin market had crashed in 1980s and due to lack of exploration and development of the land-based minerals (Lee, 2013).…”
Section: Deep Seabed Minerals As the New Mineral Resourcesmentioning
confidence: 99%
“…It has played a crucial role in the Malaysian economic development since the late 1980s (Othman & Jafari, 2012). Nevertheless, the source of oil & gas is depleting due to the impact of the production since the late 1980s (Lee, 2013).…”
Section: Deep Seabed Minerals As the New Mineral Resourcesmentioning
confidence: 99%
“…The impact of OP on energy depletion is a very relevant phenomenon as increasing OP may increase oil rents and would become a reason for over-extraction and depletion of this natural resource. Limited literature investigated the OP and natural resource depletion relationship [60][61][62][63][64]. Othman and Jafari [60] probed the role of OP on oil reserve depletion in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Limited literature investigated the OP and natural resource depletion relationship [60][61][62][63][64]. Othman and Jafari [60] probed the role of OP on oil reserve depletion in Malaysia. They found that, during rising world oil prices (2001)(2002)(2003)(2004)(2005), the oil reserves declined sharply.…”
Section: Introductionmentioning
confidence: 99%